Medium-term forecast of the age structure of teachers in secondary schools in the Russian Federation - Vasilieva, L. V.; Lebedev, K. V.; Sumenova, E. S. (Obrazovanie i nauka, 2021)
Introduction. The trend of teaching staff aging in secondary schools is evident in many countries. A negative consequence of this is the growing gap between the personal resources of teachers and the requirements of the profession. Solving the problem of maintaining an optimal age structure involves studying its dynamics and forecasting its development in order to develop measures for personnel planning. The present paper presents the results of the analysis of the current age structure of teachers in the regional context (in the subjects of the Russian Federation) and develops a forecast for its development. The aim of the current research was to present the results of the development of a medium-term (until 2024) forecast of the age structure of teachers in the subjects of the Russian Federation. Methodology and research methods. The research was based on a general scientific methodology applying a systematic approach and the methods of statistical analysis, comparison, generalisation, systematisation, structuring, interpretation, extrapolation, forecasting, and graphical representation of data. The authors analysed the data in official statistics of the Russian Federation and the Organisation for Economic Cooperation and Development. The provisions of normative and legislative documents in the field of strategic regulation of education in the Russian Federation, scientific publications of Russian and foreign researchers in the Scopus, Web of Science, and Science Index databases were investigated as well. Results. The authors identify and highlight the factors, which have the most significant impact on the current state of personnel support for educational activities in the world. The analysis of age-specific teacher characteristics in cross-country comparison is performed. The assessment of age structure of general education teaching personnel in Russia as a whole and at the regional level is carried out. The forecast for its development for the period up to 2024 is developed. Scientific novelty. The conceptual feature of the present study lies in the view of the trends in the development of age cohorts in homogeneous groups. The approach employed allows for increasing the accuracy of forecasting of teacher demand, taking into account the specifics of regional demand. Practical significance. Taking the specifics of the regions into consideration, it will be possible to improve the quality of education. The results of the research can be used by specialists in the course of conducting international research, planning teacher training, and developing measures to enhance the prestige of teaching profession and to stimulate the influx of young personnel to schools at the Federal level and in the regions of the Russian Federation.